Patients' and next of kin's expectations and experiences of a mobile integrated care model with a home health care physician - a qualitative thematic study - Lina Emmesjö; Catharina Gillsjö; Anna K. Dahl Aslan; Jenny Hallgren (BMC, 2023)
Abstract Background The organizational principle of remaining at home has offset care from the hospital to the home of the older person where care from formal and informal caregivers is needed. Globally, formal care is often organized to handle singular and sporadic health problems, leading to the need for several health care providers. The need for an integrated care model was therefore recognized by health care authorities in one county in Sweden, who created a cross-organisational integrated care model to meet these challenges. The Mobile integrated care model with a home health care physician (MICM) is a collaboration between regional and municipal health care. Descriptions of patients' and next of kin's experiences of integrated care is however lacking, motivating exploration. Method A qualitative thematic study. Data collection was done before the patients met the MICM physician, and again six months later. Results The participants expected a sense of relief when admitted to MICM, and hoped for shared responsibility, building a personal contact and continuity but experienced lack of information about what MICM was. At the follow-up interview, participants described having an easier daily life. The increased access to the health care personnel (HCP) allowed participants to let go of responsibility, and created a sense of safety through the personalised contact and continuity. However, some felt ignored and that the personnel teamed up against the patient. The MICM structure was experienced as hierarchical, which influenced the possibility to participate. However, the home visits opened up the possibility for shared decision making. Conclusion Participants had an expectation of receiving safe and coherent health care, to share responsibility, personal contact and continuity. After six months, the participants expressed that MICM had provided an easier daily life. The direct access to HCP reduced their responsibility and they had created a personalised contact with the HCP and that the individual HCP mattered to them, which could be perceived as in line with the goals in the shift to local health care. The MICM was experienced as a hierarchic structure with impact on participation, indicating that all dimensions of person-centred care were not fulfilled.